Analytical Framework for Work Package 2: Micro, Small, and Medium Enterprises (MSMEs) and the Informal Sector - Berkhout, Ezra D.; Ceballos, Francisco; de Brauw, Alan; Lundy, Mark M.; Berg, Marrit van den; Wyatt, Amanda (CGIAR System Organization, 2022)
This paper develops an analytical framework for considering food systems interventions meant to increase the supply of sustainable nutritious foods in the food environment, to improve choices faced by consumers. The framework plays close attention to issues including employment among women and youth, and possible tradeoffs with measures of environmental sustainability. It will be used for developing interventions in the SHiFT research agenda.